Attachment style, psychotic phenomena and the relationship with aggression: an investigation in a non-clinical sample - Whale, Katherine (2016)
Research has long suggested that there is a link between psychosis and aggression, but we continue to not fully understand that relationship. This paper aims to explore whether attachment, which is empirically linked to both psychosis and aggression, could be an important factor in understanding this relationship. Using a community sample, 213 participants participated in an online questionnaire and responded to measures of adult attachment, aggression and psychotic like events (PLE). Results suggest that there is a strong relationship between variables, and that attachment and PLE provide a statistically significant model for aggression. PLE are a stronger predictive factor than attachment, however a two factor model (attachment and PLE) provides a stronger predictive model compared to a single factor more (PLE alone) when looking at hostility and verbal aggression. There are differences in the relationship between symptoms of PLE, types of insecure attachment and types of aggression, hostility provides the strongest relationships with variables, and verbal aggression the weakest. Results are discussed with a view for future research and applications to models of psychosis.